The 2003 Ms6.1 Minle Earthquake: An Earthquake in the Minle-Yongchang Reverse Fault-Related Fold Belt in the Hexi Corridor, NW China - Zou, Xiaobo; Yuan, Daoyang; Shao, Yanxiu; Liu, Xingwang; Ge, Weipeng; Zhang, Bo (Frontiers in Earth Science, 2021)
The Minle-Yongchang fault is an active reverse fault related fold structural belt developed in the Hexi Corridor basin on the northeastern edge of the Tibetan Plateau. An earthquake of Ms 6.1 occurred near the Minle-Yongchang fault zone in 2003. The deformation pattern of the Minle-Yongchang fault and its relationship with this strong earthquake, however, are still not known well. In this study, we use digital elevation model (DEM) derived from SPOT 6 stereo image pair and high-precision differential GPS to measure displacements of terraces. Topography profiles along the terraces across the Minle-Yongchang fault show that high alluvial terrains exhibit fold deformation. The vertical offsets of T2 and T3 of the Tongziba river is 2 m and 22±1.5 m respectively. Optically Stimulated Luminescence dating (OSL) indicate that ages of T2 and T3 is 10 ka and 106 ka, respectively. We calculate an average uplift rate of 0.20±0.05 mm/a dividing vertical offset by ages. We use methods of Hypoinverse Absolute Location and Double-difference Location with waveform cross-correlation technology to locate precisely earthquake sequence near the epicenters of two earthquakes in 2003. A total of 383 earthquakes are precisely located. Based on the results of precise seismic positioning, using the method of determining fault plane by small earthquakes, it is found that the seismogenic fault is a low-angle thrust with strike of 311°, dip of NE and dip angle of 14°. It does not rupture surface and extend to 19-20 km in deep and be hidden under the Yonggu Anticline. We also employ Cut and Paste (CAP) method with broadband digital waveform data to determine the focal mechanism of the main shock in 2003 with strike of 311°, dip of 34° and rake of 90°. The fault plane parameters obtained by these two ways are roughly consistent. According to the results of precise location of small earthquakes, aftershocks distribution and terrace deformation in the study area, the Ms 6.1 Minle earthquake in 2003 was caused by the latest activity of a blind reverse fault related fold in Hexi Corridor basin.